Typy zmodyfikowane przestępstw z perspektywy nowelizacji kodeksu karnego z lat 2019 i 2022 : Wybrane aspekty - Brzezińska, Joanna (Wydawnictwo Uniwersytetu Wrocławskiego, 2022)
The purpose of this study is to compare the assumptions regarding the structure of the modified types of crimes found in the legislator’s proposed amendment to the 2019 Criminal Code with the currently proceeding amendment to the 2022 Criminal Law. For this purpose, the following issues were subject to analysis: new, modified varieties that are expected to appear in the Criminal Code; changes in the structure of the current regulations the legislator intends to make; the consequences to criminal law in terms of the range of criminal sanctions of modified types these modifications will cause. Based on the analysis, it was shown that the remodelling on the level of modified types will apply only to the qualified variety, which will result in a widening of the range of criminal sanctions in progressive terms (in plus), thus increasing the repressiveness of the Criminal Code.
Keywords: modified types; amendment to the Criminal Code; synthethic or casuistic regulations